Comorbidities involving parasitic diseases: A look at the benefits and complications. Issue 20 (October 2022) - Oliveira, Fabrício Marcus Silva; Cruz, Ruth Elizabeth; Pinheiro, Guilherme Rafael Gomide; Caliari, Marcelo Vidigal
Parasitic infections acquired by the population cause substantial morbidity worldwide, with individuals from developing countries being most affected. Some parasites remain in the host for long periods, settling in different organs, manipulating the flow of nutrients and metabolites, and influencing the immune response, favoring their adaptation. The host attempts to counteract the metabolic and immunological alterations and the possible damage caused by infection. These metabolic and immunological changes experienced by the host can influence the progression of other existing morbidities or those that will be acquired in the future. Cancer and metabolic diseases are also frequent causes of morbidity in the world population. The large numbers of individuals affected by cancer and metabolic diseases and the high prevalence of morbidity caused by parasitic diseases favor the development of comorbidity involving these pathologies. This review provides an overview of major advances in research on cancer and metabolic diseases associated with parasitic infections. Information about hosts and parasites such as alterations of the immune response, metabolism and adaptation mechanisms of the parasites, and parasitic molecules with therapeutic potential is provided, as well as the beneficial results or complications related to the comorbidities discussed herein. We emphasize the need to conduct additional studies addressing comorbidities associated with parasitic infections to improve the understanding of the impact of this association on the progression of morbidities, as well as the possibility of the therapeutic use of and therapeutic approaches involving parasites.